Robert D. Kaplan, The Revenge of Geography - Mr. Khusrow Akkas Abbasi (CISS Insight Journal, 2014)
Robert D. Kaplan is the Chief Geopolitical Analyst for Stratfor (a firm that deals with global intelligence issues), and a non-resident senior fellow at the Center for New American Security in Washington, D.C. He has also been a foreign correspondent for The Atlantic for over 25 years. In 2009, he was appointed to the Pentagon's Defense Policy Board, and served on the Board till end 2011. From 2006 to 2008, he remained the Class of 1960 Distinguished Visiting Professor in National Security at the U.S. Naval Academy.The main argument of Revenge of Geography by Kaplan is that geography is the prime determinant of power. The author is of the view that geography is also the only answer to the question why nations that were significant historically are still relevant today. He has comprehensively surveyed the works of scholars like James Fairgrieve, Leon Wieseltier, Professor Nicholas J. Spykman and Professors William H. McNeil and Marshall G.S. Hodgson, Sir Halford J. Mackinder, among others. These scholars have discussed in much detail the characteristics and identities of various regions such as the Rimland of Eurasia, and the Heartland.